Cardiolipin Remodeling Defects Impair Mitochondrial Architecture and Function in a Murine Model of Barth Syndrome Cardiomyopathy. (16th June 2021) - Zhu, Siting; Chen, Ze'e; Zhu, Mason; Shen, Ying; Leon, Leonardo J.; Chi, Liguo; Spinozzi, Simone; Tan, Changming; Gu, Yusu; Nguyen, Anh; Zhou, Yi; Feng, Wei; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cardiomyopathy is a major clinical feature in Barth syndrome (BTHS), an X-linked mitochondrial lipid disorder caused by mutations in Tafazzin ( TAZ ), encoding a mitochondrial acyltransferase required for cardiolipin remodeling. Despite recent description of a mouse model of BTHS cardiomyopathy, an in-depth analysis of specific lipid abnormalities and mitochondrial form and function in an in vivo BTHS cardiomyopathy model is lacking. Methods: We performed in-depth assessment of cardiac function, cardiolipin species profiles, and mitochondrial structure and function in our newly generated Taz cardiomyocyte-specific knockout mice and Cre-negative control mice (n≥3 per group). Results: Taz cardiomyocyte-specific knockout mice recapitulate typical features of BTHS and mitochondrial cardiomyopathy. Fewer than 5% of cardiomyocyte-specific knockout mice exhibited lethality before 2 months of age, with significantly enlarged hearts. More than 80% of cardiomyocyte-specific knockout displayed ventricular dilation at 16 weeks of age and survived until 50 weeks of age. Full parameter analysis of cardiac cardiolipin profiles demonstrated lower total cardiolipin concentration, abnormal cardiolipin fatty acyl composition, and elevated monolysocardiolipin to cardiolipin ratios in Taz cardiomyocyte-specific knockout, relative to controls. Mitochondrial contact site and cristae organizing system and F1F0-ATP synthase complexes, required for cristae morphogenesis, were abnormal, resulting in onion-shaped mitochondria. Organization of high molecular weight respiratory chain supercomplexes was also impaired. In keeping with observed mitochondrial abnormalities, seahorse experiments demonstrated impaired mitochondrial respiration capacity. Conclusions: Our mouse model mirrors multiple physiological and biochemical aspects of BTHS cardiomyopathy. Our results give important insights into the underlying cause of BTHS cardiomyopathy and provide a framework for testing therapeutic approaches to BTHS cardiomyopathy, or other mitochondrial-related cardiomyopathies.